2015
DOI: 10.1093/nar/gkv037
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator complex of Caenorhabditis elegans: insights into the developmental and physiological roles of a conserved transcriptional coregulator

Abstract: The Mediator multiprotein complex (‘Mediator’) is an important transcriptional coregulator that is evolutionarily conserved throughout eukaryotes. Although some Mediator subunits are essential for the transcription of all protein-coding genes, others influence the expression of only subsets of genes and participate selectively in cellular signaling pathways. Here, we review the current knowledge of Mediator subunit function in the nematode Caenorhabditis elegans, a metazoan in which established and emerging ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 124 publications
2
39
0
Order By: Relevance
“…Previous studies (reviewed in Grants et al 2015) and our data show that several core Mediator subunits promote C. elegans vulva development, whereas CKM subunits inhibit this process. This suggested that intra-Mediator regulation might coordinate gene expression downstream of the EGFR-Ras-ERK signaling pathway that drives vulva development.…”
Section: The Ckm Promotes Lin-1/ets Repressor Activitysupporting
confidence: 69%
See 3 more Smart Citations
“…Previous studies (reviewed in Grants et al 2015) and our data show that several core Mediator subunits promote C. elegans vulva development, whereas CKM subunits inhibit this process. This suggested that intra-Mediator regulation might coordinate gene expression downstream of the EGFR-Ras-ERK signaling pathway that drives vulva development.…”
Section: The Ckm Promotes Lin-1/ets Repressor Activitysupporting
confidence: 69%
“…Several Mediator subunits positively or negatively regulate EGFR signaling-driven developmental processes (reviewed in Grants et al 2015), but pertinent mechanisms remain incompletely understood. Here, we used the well-characterized vulva development paradigm in C. elegans to delineate the role of the Mediator CKM module.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, MED12 encodes a subunit of a "kinase module," which includes cyclin C and cyclindependent kinase (CDK) 8/CDK19, that belongs to a large protein complex implicated in many activities, including the regulation of transcription, chromatin architecture and enhancer-promoter gene looping in interaction with cohesin and noncoding RNA [111][112][113]. In Caenorhabditis elegans, the MED12 ortholog may work as an integration hub for several signaling pathways, including EGFR, Notch and Wnt signaling [113,114] and it has been reported to modulate the response to EGFR, ALK and BRAF inhibitors by negatively regulating transforming growth factor b (TGF-b) receptor 2 in mammalian cells [115].…”
Section: Med12 Mutationsmentioning
confidence: 99%